Phytochemical and pharmacological properties of essential oils from Cedrus species. Issue 12 (18th June 2018) - Saab, Antoine M.; Gambari, Roberto; Sacchetti, Gianni; Guerrini, Alessandra; Lampronti, Ilaria; Tacchini, Massimo; El Samrani, Antoine; Medawar, Samir; Makhlouf, Hassane; Tannoury, Mona; Abboud, Jihad; Diab-Assaf, Mona; et al.
Abstract: Natural products frequently exert pharmacological activities. The present review gives an overview of the ethnobotany, phytochemistry and pharmacology of the Cedrus genus, e.g. cytotoxic, spasmolytic immunomodulatory, antiallergic, anti-inflammatory and analgesic activities. Cancer patients frequently seek remedies from traditional medicinal plants that are believed to exert less side effects than conventional therapy with synthetic drugs. A long-lasting goal of anti-cancer and anti-microbial therapy research is to find compounds with reduced side effects compared to currently approved drugs . In this respect, Cedrus species might be of interest. The essential oil isolated from Cedrus libani leaves may bear potential for drug development due to its high concentrations of germacrene D and β -caryophyllene. The essential oils from Cedrus species also show bioactivity against bacteria and viruses. More preclinical analyses (e.g. in vivo experiments) as well as clinical trials are required to evaluate the potential of essential oils from Cedrus species for drug development. Abstract :